1994
DOI: 10.1111/j.1651-2227.1994.tb13398.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate utilization during the first weeks of life

Abstract: It is assumed that substrate utilization changes markedly around birth, from mainly glucose utilization before, to glucose/fat utilization after birth. We studied substrate oxidation and turnover in preterm infants on the first day and during the first weeks of life. We found that only part of the glucose that is infused on the first day of life is oxidized, while glucose is also converted into fat at the same time. Almost half of the energy expenditure is provided by fat oxidation on day 7 and 28 of life. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Almost half of the energy expenditure in neonates after birth is provided by fat oxidation. The rate of oxidation of medium-chain triglycerides is higher than that of long-chain fatty acids [16]. A significant negative correlation was found between erythrocyte pyruvate kinase activity and gestational age.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Almost half of the energy expenditure in neonates after birth is provided by fat oxidation. The rate of oxidation of medium-chain triglycerides is higher than that of long-chain fatty acids [16]. A significant negative correlation was found between erythrocyte pyruvate kinase activity and gestational age.…”
Section: Discussionmentioning
confidence: 62%
“…The parameters of acidobasic balance are insufficient to confirm metabolic disturbances and hyperlactacidemia in children, because the lactate level in blood neither correlates with pH nor with base excess values [24]. It is known that only a part of the glucose infused into premature neonates during the first days of life is oxidized [16]. The higher dose of insulin necessary to correct hyperglycemia in premature neonates with a low PDH activity may therefore increase the lactate level and further worsen the metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…We measured endogenous PC palmitate synthesis from glucose only. We have recently demonstrated that lipogenesis from glucose occurs in preterm infants fed solely glucose intravenously on the first day of life (29). Therefore, with our approach carbon-13 incorporation into surfactant PC occurs via lipogenesis in type II cells directly or via lipogenesis in the liver and subsequent uptake of labeled palmitic acid by type II cells.…”
Section: Discussionmentioning
confidence: 99%
“…On a per gram basis, Intralipid is a very important source of energy, providing nearly three times that of glucose. Thus, providing glucose at a rate equivalent to the basal glucose turnover rate of these infants (6 -8 mg/kg/min or 33-44 mol/ kg/min) in addition to currently recommended rates of lipid (~3 g/kg/d on d 3-4 of life) and amino acid substrate (important for protein synthesis) (~3 g/kg/d) may be a potential strategy to reduce the risk of hyperglycemia without increasing the risk of either energy insufficiency (27,28) or hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%